SPIDERS (ARANEAE) OF THE DELIBLATO SANDS (SERBIA) (Acta Entomologica Serbica, 2019)
The Special Nature Reserve “Deliblato Sands” in Serbia is the largest European continental sand area situated between the Danube River and western Carpathian slopes. Forestation, agriculture and fire are the main threats to this landscape. While plants and vertebrates are well known in this area, spiders were researched for the first time. Collecting with pitfall traps, sweep nets and beating in four different habitat types during a whole vegetation period yielded 1120 adult specimens and 96 species. Eight species represent first records for the Serbian fauna: Atypus muralis Bertkau, 1890, Gnaphosa muscorum (L. Koch, 1866), Zelotes segrex (Simon, 1878), Mecopisthes peusi Wunderlich, 1992, Oxyopes heterophthalmus (Latreille, 1804), Heliophanus lineiventris Simon, 1868, Simitidion simile (C. L. Koch, 1836) and Xysticus mongolicus Schenkel, 1963. In our study, six of these species were restricted to the open sandy habitat, highlighting the special importance of this unique habitat type.